Modulation of plant acetyl-CoA synthetase activity by post-translational lysine acetylation - Sofeo, Naazneen; Winkelman, Dirk C.; Leung, Karina; Nikolau, Basil J. (Frontiers in Molecular Biosciences, 2023)
Acetyl-CoA synthetase (ACS) is one of several enzymes that generate the key metabolic intermediate, acetyl-CoA. In microbes and mammals ACS activity is regulated by the post-translational acetylation of a key lysine residue. ACS in plant cells is part of a two-enzyme system that maintains acetate homeostasis, but its post-translational regulation is unknown. This study demonstrates that the plant ACS activity can be regulated by the acetylation of a specific lysine residue that is positioned in a homologous position as the microbial and mammalian ACS sequences that regulates ACS activity, occurring in the middle of a conserved motif, near the carboxyl-end of the protein. The inhibitory effect of the acetylation of residue Lys-622 of the Arabidopsis ACS was demonstrated by site-directed mutagenesis of this residue, including its genetic substitution with the non-canonical N-ε-acetyl-lysine residue. This latter modification lowered the catalytic efficiency of the enzyme by a factor of more than 500-fold. Michaelis-Menten kinetic analysis of the mutant enzyme indicates that this acetylation affects the first half-reaction of the ACS catalyzed reaction, namely the formation of the acetyl adenylate enzyme intermediate. The post-translational acetylation of the plant ACS could affect acetate flux in the plastids and overall acetate homeostasis.